Preliminary Study Of Introduction Of Barn Owls (Tyto Alba Javanica) In Pulau Rawa And Their Interaction With Rat Populations On The Island - Ravindran, R. Shakinah M. (2020)
This study was carried out to introduce Southeast Asian barn owls (Tyto alba javanica) to the island of Pulau Rawa and to study their interaction with the rat population on the island. Nine barn owls of four different backgrounds were introduced on the island intermittently throughout the one-year study period. The nine owls consisted of wild adult owls (n=2), wild fledglings (n=2), captive-held owls (n=2) and hand-reared owls (n=3). Barn owl releases were considered successful when owls were traceable more than 30 days after release. All wild adult owls and hand-reared owls were tracked for more than two weeks but less than 30 days post-release, and one female hand-reared owl was tracked for more than 30 days post-release and throughout the study. The remaining owls (n=4) were tracked less than two weeks post-release. When tracking results were sufficient, ranging behaviour of released owls, i.e. home range, core area, area of use, habitat preference, roost sites and movement, were analysed. Live-trapping of rats in relation to barn owl releases were carried out at three trapping sites throughout the study and capture rate was used as an index to estimate the rat abundance on the island. Wild adult owls (n=2) had an average home range of 0.039 km2 (± 0.014 km2) and an average core area of 0.0055 km2 (±0.0002 km2). Hand-reared owls (n=2) had an average estimated home range of 0.035 km2 (±0.003 km2) and an average core area of 0.002 km2 (±0.0001 km2). The preferred habitat within the island and within the home range for most owls were forest areas and the most preferred roost sites for all owls were trees within the forest.